2007
DOI: 10.1108/14637150710740491
|View full text |Cite
|
Sign up to set email alerts
|

The influence of external variables on the executives' use of the internet

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
(91 reference statements)
5
19
0
Order By: Relevance
“…The combination of uncertainty (likelihood of loss) and danger (cost of the loss), which are components of perceived risk, reduce perceived usefulness and adoption. This relation has also been found by Cheng et al (2006) and Seyal and Rahman (2007), so that the greater the perceived risk, the lower the perceived value of use of the system to acquire the product. Previous studies have found that ease of use reduces the uncertainty and risk of system use (Feathernan and Pavlou, 2003).…”
Section: Perceived Shopping Riskmentioning
confidence: 54%
“…The combination of uncertainty (likelihood of loss) and danger (cost of the loss), which are components of perceived risk, reduce perceived usefulness and adoption. This relation has also been found by Cheng et al (2006) and Seyal and Rahman (2007), so that the greater the perceived risk, the lower the perceived value of use of the system to acquire the product. Previous studies have found that ease of use reduces the uncertainty and risk of system use (Feathernan and Pavlou, 2003).…”
Section: Perceived Shopping Riskmentioning
confidence: 54%
“…Based on his definition, Adams et al [1] and Davis [8] find perceived usefulness to be a major determinant of use behavior and intention. Perceived usefulness was found to have positively influenced the behavioral intention to use a computer system [14,16,17,19,20,33,39,41,45]. Subramanian [42] reaffirms two salient belief measurements (perceived usefulness and perceived ease of use), using a new data set for two different technologies, and finds that PU, instead of PEU, has a direct effect on use behavior employing structural equation modeling (SEM).…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 78%
“…In fact, effectively accessing music and relevant information has become one of the key benefits sought by online music consumers. Perceived Usefulness was found to have positively influenced the Behavioural Intention to use a computer system (Fagan, Wooldridge, & Neill, 2008;Guriting & Ndubisi, 2006;Ha & Stoel, 2009;Hsu, Wang, & Chiu, 2009;Huang, 2008;Norazah, Ramayah, & Norbayah, 2008;Norazah, Ramayah, & Michelle, 2010;Ruiz-Mafe´, SanzBlas, Aldas-Manzano, 2009;Seyal & Rahman, 2007;Tong, 2009). Hence, this study believes that Perceived Value will increase with Perceived Usefulness of online music.…”
Section: Perceived Usefulnessmentioning
confidence: 99%